APLIKASI MODEL BISNIS KANVAS, STRATEGI BISNIS, DAN ANALISIS KELAYAKAN KEUANGAN STUDI KASUS PADA BISNIS BARU “CAPTUREBOX” PHOTOGRAPHY - Petrus Pius Salamin; Francisca Hermawan; Juniardy Saputra Tanurrezal (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2018)
Abstract, This analysis aims to (1) describe how Canvas Business Model can be applied to a new fotography business, (2) choice what business strategies needed to be applied to achieve the vision, mission and the objective of this business, (3) examine its fianacial feasibility. The sales data used is the projection data as a result of market opportunity analys for the next five years. Pricing Method used is murkup (markon), with taking into account the future economic conditions and the profit to be earned. The business financial feasibility is measured with Net Present Value (NPV), Payback Period, and Profitability Indexmethods. The result shows that the Canvas Busines Model can be applied to this business. The Net profit in 2018 is projected Rp.217.870.000, andit will increase to Rp 961.845.000 in the yaer of 2021, with average growth of 46 % per year. However this must be supported by an appropriate marketing strategy, i.e. product, price, promotion, and place/distrubtion strategies. From the point of view of Present Value, PayBack Period, anf Profitability Index, it is obvious that this business is feasible. The NPV is positive Rp 1.602.687.876. The PI is (11.85) >1. The Pay Back Period is only six (7) months.